Histological, histochemical and morphometric study of female corpora allata of Pachycondyla striata ants (Hymenoptera: Ponerinae) - Forster Figueira, Cristiano Ricardo [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (My University, 2002)
In this study we utilized both histological/histochemical tests and morphometric/statistical tests to observe developmental differences in the corpora allata in Pachycondyla striata workers and queens ants. The general structure of corpora allata was similar between workers and queens. The differences found among the volumes was not statistically significant when the probability value was set at 5%. Although the queen corpora allata volume has been observed smaller than those of the worker and the right gland volume has been smaller than those of the left one. Differences also were observed histologically, the worker corpora allata cells showed homogeneous cytoplasm and sparse nuclear chromatin in well defined nuclei. It was the reverse in the queens, in which the corpora allata cells showed some secretory cytoplasmic vesicles and nuclei with a different morphology, i. e., from extremely large with sparse chromatin to small with condensed chromatin. Employing histochemical tests verified that the corpora allata in both castes contained large amounts of RNA and protein in the cytoplasm of their cells and an absence of polysaccharides. Differences in the lipid amounts in worker's glands were found, whereas, in the queens' corpora allata lipids always occur.
Keywords: Ants; Corpora allata; Ovarian development; Pachycondyla striata; Formicidae; Hymenoptera; Invertebrata; Ponerinae